AKSEPTABILITAS BUBUK MULTI-ZAT-GIZI-MIKRO OLEH BALITA KELUARGA MISKIN DI JAKARTA UTARA - Nurfi Afriansyah; Hermina Hermina; Ema Luciasari; Yurista Permanasari; Noviati Fuada; Abas B. Jauhari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
Acceptability of Multiple-Micronutrient Powders By Under-Fives of Poor Families In North Jakarta.Background: The final of three steps in developing the Indonesia Multiple-Micronutrient Powders (MMP) called TABURIA was to evaluate its effectiveness in improving the nutritional status of under-fives under programmatic setting. Together with execution of the final step, it was also necessary to conduct the subject's perception, satisfaction, and expectation toward TABURIA.Objectives: To find-out the acceptability of under-fives' mothers toward TABURIA.Methods: We assessed the acceptability of TABURIA for under-fives of poor families in North Jakarta. This under-fives beneficiaries of the MMP project participating in "the Effectiveness of TABURIA on Growth and Hemoglobin Concentration Study" were surveyed about the acceptability of TABURIA (n = 464). Acceptability of the MMP was evaluated based on mothers' perceptions and experiences with organoleptic qualities, ease of use, perceived satisfaction, and expectation. The median Likert scale ranking of organoleptic and use qualities for TABURIA was "I liked it" (3 on a scale of 1-5). However, responses to openended survey questions and semi-structured interviews showed decided preferences.Results: TABURIA was strongly preferred by under-fives. In interviews, most of mothers expressed like of the texture, color, odor, and taste of TABURIA; they found it practical to get, store and prepare, and reported the satisfaction and expectation with it.Conclusions: Most of under-fives' mothers were very like TABURIA product. They stated TABURIA was simple to use, more preferred it than the other consumed supplement products, willing to pay if it will be sold to the free market; they preferred to pay it maximum Rp 500 per sachet. They required TABURIA, especially for generating their children appetite.Keywords: Multiple-Micronutrient Powders (MMP), acceptability, under-fives.